EVALUASI SISTEM REMUNERASI DOSEN BADAN LAYANAN UMUM PERGURUAN TINGGI (Studi Kasus Universitas “X”) - Vidia Alif Agrimahera; Helmy Adam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to evaluate lecturer remuneration system in University’s Public Service Agency. The Evaluation process is conducted based on the observance of laws and regulations. This research uses qualitative descriptive method. Researcher as the key instrument. The data obtained through interviews and document collection. The result of the research show that the remuneration system “X” University meets the principle of fair, equitable and reasonable. The principle of proportionality, equality and appropriateness in accordance to PP Nomor 23 Tahun 2005 and PMK Nomor 10 Tahun 2006. legislation and regulations. But a lack of transparency and a single salary. Nevertheless the principle of transparency and the single salary has not been carried out in accordance with laws and regulations. Researchers propose model of remuneration in accordance with the regulations. Keywords: remuneration, Public Service Agency, university, lecturer